PENGARUH PRODUKTIVITAS LAHAN DAN NILAI TAMBAH TERHADAP DAYA SAING KOMODITAS MINYAK KELAPA SAWIT INDONESIA - Richo Melchiory Gultom (Department of Development Economics, Universitas Sriwijaya, 2012)
The purpose of this study is to investigate how the influence of area land productivity and value added on the competitiveness of the crude palm oil commodity Indonesia. The data used in this research is secondary data, consisting of output value, value added, intermediate costs, prices, export value of Indonesian palm oil commodity, the total export value of Indonesia as a whole, the total value of the world’s export palm oil commodity and total value of world export during the period for 1989 to 2008. The basic theory used is the theory of productivity, value added, efficiency and competitiveness. Regression analysis showed a positive and significant effect of field productivity and value added for competitiveness. Competitiveness can be influenced by area land productivity and value added of 67 %, and 33 % influenced by other variables. Keywords: Area Land Productivity, Value Added, Efficiency, Competitiveness, Export.